Highly dense linkage maps from 31 full-sibling families of turbot (Scophthalmus maximus) provide insights into recombination patterns and chromosome rearrangements throughout a newly refined genome assembly. (11th June 2018) - Maroso, F; Hermida, M; Millán, A; Blanco, A; Saura, M; Fernández, A; Dalla Rovere, G; Bargelloni, L; Cabaleiro, S; Villanueva, B; Bouza, C; Martínez, P
Abstract: Highly dense linkage maps enable positioning thousands of landmarks useful for anchoring the whole genome and for analysing genome properties. Turbot is the most important cultured flatfish worldwide and breeding programs in the fifth generation of selection are targeted to improve growth rate, obtain disease resistant broodstock and understand sex determination to control sex ratio. Using a Restriction-site Associated DNA approach, we genotyped 18, 214 single nucleotide polymorphism in 1, 268 turbot individuals from 31 full-sibling families. Individual linkage maps were combined to obtain a male, female and species consensus maps. The turbot consensus map contained 11, 845 markers distributed across 22 linkage groups representing a total normalised length of 3, 753.9 cM. The turbot genome was anchored to this map, and scaffolds representing 96% of the assembly were ordered and oriented to obtain the expected 22 megascaffolds according to its karyotype. Recombination rate was lower in males, especially around centromeres, and pairwise comparison of 44 individual maps suggested chromosome polymorphism at specific genomic regions. Genome comparison across flatfish provided new evidence on karyotype reorganisations occurring across the evolution of this fish group.